Fibromyalgia in patients infected with HTLV-1 and HTLV-2 - Inomata Silva, Bianca Lumi; da Cunha Rodrigues, Francisco Erivan; Tsukimata, Márcio Yutaka; Botelho, Bruno José Sarmento; Santos, Luciana Cristina Coelho; dos Santos Pereira Neto, Gabriel; Lima, Aline Cecy Rocha; André, Natália Pinheiro; Galdino, Sarah Marques; Monteiro, Danniele Chagas; Yoshikawa, Gilberto Toshimitsu; Mendonça, Leonardo Teixeira; et al. (Frontiers in Medicine, 2024)
Background Reports on the association between HTLV-2 infection and the development of diseases in the human host are rare, which has led the scientific community to believe that HTLV-2 is not an important etiological agent of lymphoproliferative or neurodegenerative disorders, which is the case for HTLV-1. In the present study, we demonstrated cases of fibromyalgia in HTLV-1 carriers and, in an unprecedented finding, in two patients with confirmed HTLV-2 infection. Methods A total of 957 individuals visited the Virology Laboratory at the Federal University of Pará for screening and confirmation tests for HTLV-1/2 infection. Individuals with confirmed HTLV-1 and HTLV-2 infection were clinically evaluated for signs and symptoms associated with infection. Results Sixty-nine individuals (7.2%) were identified as positive for HTLV infection, with 56 confirmed cases of HTLV-1 infection (5.9%), 12 cases of HTLV-2 infection (1.2%) and one case classified as undetermined (0.1%). Sixteen (23.2%) of these patients presented with rheumatological signs and complained of diffuse pain throughout the body; 12 of whom were infected by HTLV-1 (75%) and 4 were infected by HTLV-2 (25%). After anamnesis and careful evaluation, four patients were diagnosed with fibromyalgia, two of whom were infected by HTLV-1 (16.7%; 2/12) and two by HTLV-2 (50%; 2/4). The clinical follow-up and laboratory analysis results are reported in detail in this paper. Conclusion Considering the clinical cases presented herein as the first reports of patients with HTLV-2 infection with clinical symptoms of fibromyalgia, the importance of further studies on the pathogenicity of HTLV-2, similar to what have already been performed for HTLV-1, is highlighted. Our results also confirm previous evidence of an association between HTLV-1 infection and fibromyalgia.